Pengaruh Kualitas Pelayanan terhadap Kepuasan Nasabah Lembaga Perkreditan Desa (LPD) di Wilayah Kecamatan Denpasar Selatan - JUNIARTHA, I KOMANG DEDY; SUAMBA, I KETUT; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Effect of Service Quality on Village Credit Institution (LPD) Customer Satisfaction in the District of South Denpasar.  Customer satisfaction is very important for institutions that engage in financial services because good service plays a major role in providing customer satisfaction. This study aims to determine the characteristics of customers, the level of customer satisfaction on services and the influence of service quality on customer satisfaction in three Village Credit Institutions  ( LPD) in South Denpasar District. The sampling technique used in this study is proportional random sampling technique. The analysis technique used is multiple linear regression analysis. The result shows that tangible, reliability, responsiveness, assurance, and empathy have a significant effect on customer satisfaction in the LPDs in the South Denpasar District. Customers are mostly females between 41 - 50 years old with an education level of high school (SMA) / equivalent, and work as private employees. The level of customer satisfaction on the services of the LPDs in the District of South Denpasar is in the very satisfied category. Service quality, namely; tangible, reliability, responsiveness, assurance, and empathy have a positive and significant effect on customer satisfaction on the LPDs in the District of South Denpasar, The LPDs should pay more attention, appropriately solve problems and quickly respond to customers to increase customer satisfaction.